Protest camps in international context : spaces, infrastructures and media of resistance / edited by Gavin Brown, Anna Feigenbaum, Fabian Frenzel, Patrick McCurdy. - Brown, Gavin (Lecturer in Human Geography); Frenzel, Fabian, 1975-; Feigenbaum, Anna (Policy Press, 2017)
Through a series of interdisciplinary case studies, this topical collection is the first to focus on protest camps as unique organisational forms that transcend particular social movements' contexts. The book offers a critical understanding of current protest events and will help to better understand new global forms of democracy in action.